English-Indonesian Deviation On Translation Of Eclipse Novel - Pujiati, Tri; Arjulayana, Arjulayana (Globish: An English-Indonesian Journal for English, Education, and Culture, 2025)
This study uses a qualitative descriptive approach with content analysis methods on novels translated from English into Indonesian. This study was conducted to investigate the type of translation deviation at the syntactic level, in the question sentences used in dialogue of Stephenie Meyer’s Eclipse novel. The source data on the study was taken from Eclipse novel as the source text and Gerhana novel as the target text. The novel has a good translation result, but there are some grammatical deviations when translated into the target text. Translation deviations by using Newmark’s theory. The results of the study showed that (1) translation deviations found in question sentences that are syntactic, lexical, and word arrangement deviations; (2) the causes of such deviations are (1) the presence of untranslated words, grammatical errors, and the use of individual languages; (3) the impact of these deviations is that the sentence becomes ungrammatical, the sentence is not commensurate, there is interference in Indonesian, the text is impolite, the text is ambiguous, and the text is unclear. In general, it can be concluded that the occurrence of deviations at this syntactic level has more influence on the grammatical aspect due to the difference in sentence structure in two different languages. Translators strive to translate the text so that it is easily understood by the reader and adapted to the target reader so that many grammatical aspects are not translated.